2010
DOI: 10.12968/jowc.2010.19.3.47279
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a two-component compression system for the therapy of venous leg ulcers

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…The same search, as previously described, allowed us to retrieve nine publications reporting on time to wound closure (either mean or median) varying from 5 to 6 weeks up to 1 year. 32,36,40,53,[57][58][59][60][61] The BioPhotonic System performed well when compared with other treatments in terms of closure rates and time to wound closure. Furthermore, its treatment regimen led to a high rate of compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The same search, as previously described, allowed us to retrieve nine publications reporting on time to wound closure (either mean or median) varying from 5 to 6 weeks up to 1 year. 32,36,40,53,[57][58][59][60][61] The BioPhotonic System performed well when compared with other treatments in terms of closure rates and time to wound closure. Furthermore, its treatment regimen led to a high rate of compliance.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies of wound assessment and treatment such as compression therapy (Escaleira, Cardoso, Rego, Macedo, & Midoes, 2010), how to treat infected wounds (O'Meara, Al-Kurdi, Ologun, & Ovington, 2010), different dressings and wound healing (Lazareth et al, 2007), and the relation between pain and wound healing (Woo & Sibbald, 2009). The complexity of the wound treatment is noticed and so is the importance of a prophylactic consent.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line with the observational study by Escaleira et al [38] who included ulcers varying in size from large to small and of durations from short to long and found that this accounted for a significant variance in HTs in the study. However, this study by Escaleira et al [37] is different from the reviewed studies because the medical dressings were applied before the bandage compression, which can contribute to positive HT findings. Small ulcers with short durations are more likely to heal, and their inclusion in the studies can shorten HT [38].…”
Section: Discussionmentioning
confidence: 86%